2012
DOI: 10.1002/jms.2026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the major urinary metabolites in man of seven synthetic cannabinoids of the aminoalkylindole type present as adulterants in ‘herbal mixtures’ using LC‐MS/MS techniques

Abstract: Herbal mixtures, such as 'Spice', containing cannabimimetic compounds are easily available on the Internet and have become increasingly popular among people having to undergo urine drug testing, as these compounds are not detected by current immunochemical tests. For analysis of urine samples, knowledge of the main metabolites is necessary as the unchanged compounds are usually not found in urine after consumption. In this paper, the identification of the major metabolites of the currently most common seven sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
101
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 25 publications
18
101
3
2
Order By: Relevance
“…We and others have identified several hydroxylated metabolites of JWH-018 and AM2201 in humans with a known history of K2 use, implicating the role of mixedfunction oxidases, such as cytochromes P450, in the biotransformation of synthetic cannabinoids (Zhang et al, 2002;Sobolevsky et al, 2010;Wintermeyer et al, 2010;Chimalakonda et al, 2011b;Hutter et al, 2012). Previous reports showed that JWH-018 undergoes hepatic metabolism, leading to the formation of several naphthalene, indole, and alkyl side chain hydroxylated and carboxylated metabolites (Fig.…”
Section: Introductionmentioning
confidence: 82%
“…We and others have identified several hydroxylated metabolites of JWH-018 and AM2201 in humans with a known history of K2 use, implicating the role of mixedfunction oxidases, such as cytochromes P450, in the biotransformation of synthetic cannabinoids (Zhang et al, 2002;Sobolevsky et al, 2010;Wintermeyer et al, 2010;Chimalakonda et al, 2011b;Hutter et al, 2012). Previous reports showed that JWH-018 undergoes hepatic metabolism, leading to the formation of several naphthalene, indole, and alkyl side chain hydroxylated and carboxylated metabolites (Fig.…”
Section: Introductionmentioning
confidence: 82%
“…Further, it is necessary to identify the most prevalent metabolites for synthesis of reference standards for analytical method development. Since the first appearance of synthetic cannabinoids, many metabolism studies with human liver microsomes (HLM), human hepatocytes, and/or authentic specimens elucidated their metabolic pathways (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Most synthetic cannabinoids are eliminated via CYP metabolism, with further glucuronidation by UDPGT (phase II enzymes). Oxidative metabolites and glucuronide conjugates predominate with negligible parent compound present in human urine (16)(17)(18). Thus, it is essential to characterize metabolic profiles of synthetic cannabinoids to identify target analytes that effectively document their consumption during clinical and forensic urine testing.…”
Section: Introductionmentioning
confidence: 99%